Sovereign defaults Evidence on the importance of government effectiveness - Fournier, Jean-Marc (OECD Economics Department Working Papers, 2018)
This paper provides robust empirical evidence that government effectiveness is a key determinant of sovereign defaults. Government effectiveness is measured by a broad-based perception index of the Worldwide Governance Indicators database (WGI) disseminated by the World Bank. Public debt and sovereign default data cover both external and internal government debt. In a systematic and demanding robustness check with any possible sub-sample of a large set of control variables, the effect of government effectiveness is almost always robust. In addition, the effects of the five other main indicators of the WGI database on default risk are also investigated, showing that the rule of law, regulatory quality, control of corruption and voice and accountability are also robustly linked with default risk. Regressions with the mortality of settlers as an instrument indicate a causal effect from government effectiveness to sovereign default